HISTORY AND DEVELOPMENT OF TAFSIR IN SOUTHEAST ASIA (Indonesia, Malaysia, Brunei Darussalam, Singapore and Thailand) - Amirulloh Sain Asari (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2016)
This paper describes the history and development of tafsir in Southeast Asia, namely Indonesia, Malaysia, Brunei Darusalam, Singapore and Thailand, aimed at providing a new discourse to the academic world, that Islam has another treasure in Far Asia, which is known as a pluralistic country because Islam entered in those countries without any wars. And to provide information related the books, author influence, and method of their tafsir in general.Keyword: History, Development Tafsir, and Southeast Asia